Influence of dopant ions on properties of conducting polypyrrole and its electrocatalytic activity towards methanol oxidation - Adhikari, Arindam; Radhakrishnan, S.; Patil, Rahul (Synthetic Metals, 2009)
The polypyrrole (PPy) films were deposited on vacuum metallized substrates by electro-oxidation of pyrrole monomer. These electrodes were then modified with a range of metal halides having different electronegativities. The modified polypyrrole electrodes were employed to investigate electrocatalytic activity towards methanol electrochemical oxidation by means of cyclic voltammetry in 0.1 M HClO(4) as supporting electrolyte. It was found that the electronegativity of the dopant ion incorporated in the PPy film governs the electrocatalytic activity towards methanol oxidation. Among different dopant anions used in the present work, the PPy doped with zirconium chloride gave the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. Electrical property and the charge created due to doping in the polymers were measured using X-ray photoelectron spectroscopy (XPS) and Electron spin resonance spectroscopy (ESR). Electrocatalytic activity of the modified electrodes was correlated with various factors obtained from different polymer characterization experiments. The results were explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: charge transfer; electrocatalyst; ESR; Metal halide dopant; Methanol oxidation; polypyrrole; XPS